Auswirkungen der SARS-CoV‑2-Pandemie auf die universitäre Hals-Nasen-Ohren-Heilkunde im Bereich der Forschung, Lehre und Weiterbildung - Stöver, T.; Dazert, S.; Plontke, S. K.; Kramer, S.; Ambrosch, P.; Arens, C.; Betz, C.; Beutner, D.; Bohr, C.; Bruchhage, K. L.; Canis, M.; Dietz, A.; et al. (HNO, 2021)
Background: From spring 2020, SARS-CoV‑2 began to spread worldwide, with what is now known as the first wave of the pandemic, starting in March 2020. This resulted in restructuring and shift of resources at many hospitals. The aim of our work was to detect the effects of the pandemic on the german Oto-Rhino-Laryngology (ORL) university hospitals in terms of research, student teaching and further specialist training. Material and methods: The chairmen of the 39 ORL university hospitals in Germany were asked about the effects of the pandemic on research, student teaching and ORL specialist training (residency) in the period from March to April 2020 using a structured online survey. Results: All 39 chairmen took part in the survey. Of these, 74.4% (29/39) stated that their research activities had deteriorated as a result of the pandemic. In 61.5% (24/39) pandemic-related research issues were addressed. All hospitals reported a restriction for in-house teaching and 97.5% (38/39) introduced new digital teaching methods. During the observation period, 74.4% of the chairmen did not see ORL specialist training (residency)at risk. Conclusion: Our results provide an insight into the heterogeneous effects of the pandemic. The fast processing of pandemic-related research topics and the introduction of innovative digital concepts for student teaching impressively demonstrates the great innovative potential and the ability of the ORL university hospitals to react quickly in order to maintain their tasks in research, student teaching and ORL specialist training in the best possible way even during the pandemic.
CRIS-Team Scopus Importer:2021-02-05
Keywords: COVID-19; ORL; Otorhinolaryngology; Research; Residency; SARS-CoV‑2 pandemic; Specialist training; Teaching; University hospitals